Thirty Minutes of Running Exercise Decreases T2 Signal Intensity but Not Thickness of the Knee Joint Cartilage: A 3.0-T Magnetic Resonance Imaging Study. (October 2019) - Karanfil, Yiğitcan; Babayeva, Naila; Dönmez, Gürhan; Diren, H. Barış; Eryılmaz, Muzaffer; Doral, Mahmut Nedim; Korkusuz, Feza
Objective: Recent studies showed a potential of magnetic resonance imaging (MRI), which can be used as an additional tool for diagnosing cartilage degeneration in the early stage. We designed a cross-sectional study in order to evaluate knee joint cartilage adaptation to running, using 3.0-T MRI equipped with the 3-dimensional turbo spin echo (VISTA = Volume ISotropic Turbo spin echo Acquisition) software. By this thickness (mm) and signal intensity (mean pixel value) can be quantified, which could be closely related to the fluid content of the knee joint cartilage, before and after running. Methods: A total of 22 males, aged 18 to 35 years, dominant (right) and nondominant (left) knees were assessed before and after 30 minutes of running. Cartilage thickness and signal intensity of surfaces of the patella, medial and lateral femoral and tibial condyles were measured. Results: Cartilage thickness of the lateral condyle decreased at the dominant knee, while it increased at the medial tibial plateau. Signal intensity decreased at all locations, except the lateral patella in both knees. The most obvious decrease in signal intensity (10.6%) was at the medial tibial plateau from 949.8 to 849.0 of the dominant knee. Conclusion: There was an increase in thickness measurements and decrease in signal intensity in medial tibial plateau of the dominant knee after 30 minutes of running. This outcome could be related to fluid outflow from the tissue. Greater reductions in the medial tibial plateau cartilage indicate greater load sharing by these areas of the joint during a 30-minute running.